Malta's economy on the path to the Euro - Central Bank of Malta (Central Bank of Malta, 2007)
With a GDP of around exteuro5.1 billion and a population of 400,000 living in an area of 316 km2, Malta is the smallest and most densely populated EU Member State. In 2006 it had the fifth most open economy in the EU, and its average trade-to-GDP ratio hovered around 81% in recent years. These characteristics constitute a challenge for both policymakers and analysts in that key economic variables are prone to volatility, being highly sensitive to external events and to shocks in specific sectors or individual enterprises which, though small in absolute terms, can have a disproportionately large impact in a small country context.
Keywords: 330